Bacterial Pathogens Survival Strategies – The Haem Biosynthesis Pathway in Campylobacter jejuni - Pereira, Jessica Filipa Monteiro Martins (2021)
Campylobacter jejuni is one of the most common foodborne pathogens responsible for the majority of the worldwide diarrhoeal infections, causing illness to more than 137 million people every year according with World Health Organization. Despite its widespread and persistence, the essential molecular mechanisms for C. jejuni successful development and infection of the host are still poorly understood. This is the case of haem homeostasis, which is an essential process to bacterial development and plays a very important role during the infection process. Haem is an iron-containing porphyrin that is abundantly present in all life domains and acts as a prosthetic group for a diverse group of proteins. Haem can be either endogenously synthesised or acquired from the host. This work aims to identify and characterise C. jejuni’s haem biosynthesis pathway to better understand the role of haem biosynthesis in C. jejuni’s pathogenicity. In this work, I cloned the putative genes constituting the haem biosynthetic pathway of C. jejuni in plasmids designed for E. coli overexpression. To analyse the activity of each of the enzymes of the pathway, I complemented E. coli’s haem biosynthesis mutants with C. jejuni’s enzymes. Our results showed that C. jejuni’s genome encodes for a complete Protoporphyrin Dependent Pathway (PPD). It was further confirmed that UroD and PpfC enzymes possessed uroporphyrinogen decarboxylase and protoporphyrin ferrochelatase activities, respectively. Overall, our results strongly suggest that C. jejuni encode for a full functional PPD haem biosynthesis pathway. Further work should aim at the study of the role of these proteins in C. jejuni’s infection development.